Työnohjaajan ja ryhmän vuorovaikutus työnohjaajan työtapojen osalta heikoksi arvioiduissa etätyönohjausistunnoissa - Knuuti, Jessica; Heikkinen, Suvi (2023)
The goal of this thesis was to survey communicational phenomena from clinical supervision group sessions where one or more participants had evaluated the methods of the clinical supervisor as weak on the evaluation form. The material of this thesis consisted of video recordings of remotely implemented group clinical supervision sessions which are part of a study which was carried out in collaboration between the University of Jyväskylä and the University of Oulu PhInGain: Reducing strain and increasing gain of remote work group meetings with physiological indicators. As a research method we used conversation analysis in the analysis of the videos. Our assumption was that there could be found similar communicational phenomena between sessions in which the methods of clinical supervisor were evaluated as weak. We identified four different phenomena that emerged from the sessions where methods of the clinical supervisor were evaluated as weak: the clinical supervisors position of not-knowing does not actualize, the clinical supervisor divides the turns of speaking in a way that is inappropriate for the situation, the clinical supervisor pauses their questions unclearly, and the clinical supervisor takes position of the speaker by talking over the current speaker. In addition, our results showed that disturbances related to remoteness emerged repeatedly in sessions which had been evaluated as weak in terms of the methods of the clinical supervisor. Clinical supervisor’s choices in their procedures, interaction and positioning can affect how the participants experience the methods of the clinical supervisor. Clinical supervisors should consider when to give direct advices to participants. Our results show that after direct advices participants can withdraw from the conversation or the conversation may drift in the wrong direction. By distributing speaking turns inappropriately, clinical supervisors may delay, or even completely block participants' aim to take speakers' positions in the current conversation. Incoherently interluded questions may hinder the natural flow of the conversation when speakers and listeners positions commingle. Clinical supervisor may try to take speakers position by speaking over the currently speaking participant, which may be harmful in the perspective of the participants. Our results show that in these kinds of situations participants can show frustration or withdraw from the conversation. In addition, it is good to be aware of the additional dimensions of remote sessions, like challenges created by the usage of microphone or other technical difficulties, while implementing remote group sessions as they can cause disturbances in concentration and withdrawal from a conversation. Clinical supervisors can utilize the results of this thesis to make more aware choices about their methods and how they position themselves in the interaction of remote group clinical supervision sessions.